RISK ASSESSMENT AND RISK MITIGATION OF E-LEARNING IMPLEMENTATION IN THE MIDDLE SCHOOL USING FAILURE MODES AND EFFECTS ANALYSIS (FMEA) - Feby Artwodini Muqtadiroh; Eko Wahyu Tyas Darmaningrat; Riza Nadia Savira (UIN Sultan Syarif Kasim Riau, 2017)
An e-learning implementation is part of software implementation. In Software Development Life Cycle (SDLC), implementation is the phase after software being develoved and tested. Unfortunately, even software has been developed and tested, there has been quite number of failure stories in the implementation of e-learning.E-learning implementation concerns with three main activities: delivery, support, and feedback. To assure the success of e-learning implementation, it requires careful plans and proper and systematic implementation phases since there will a quite degree of possibilities of uncertainties and risks that may hinder successful implementation of e-learning.One of the methods adoptable to prevent failures in e-learning implementation is risk analysis. Due to those purposes, this research contributed to any institutions planning to implement e-learning to be better prepare and identify what kind of risks that may arise in the process of e-learning implementation and proper risk mitigation plan in order to be able to prevent the failure.This research has identified 24 risks that may hinder successful implementation of e-learning. And for those risks there will be choosen the high-risk activity in implementing e-learning using the Failure Modes and Effects Analysis (FMEA). There are 3-prioritized risks; very high, high, fair. And this research focuses on the very high and high degree of potential RPN are: resistance from the users due to non-involvement in the process of need identification leading to generation of final products that are not in compliance with the users, lack of policies to obligate the adoption of e-learning in learning processes, and unwillingness of the users to change to use e-learning.